(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
After the birth of the baby, a major change occurs in the vascular system: the placental circulation suddenly switches to the pulmonary circulation. The lungs, pulmonary artery and veins begin to function. After birth, the umbilical vessels that were tied are released: the umbilical vein trunk changes to the hepatic circular bundle, the umbilical arteries to the right and left lateral umbilical bundles, and the arterial fissure is preserved in its initial parts. These umbilical bundles are located on the posterior surface of the anterior abdominal wall. The venous duct is connected to the venous bundle, and the arterial duct, which connects the fetal pulmonary trunk with the curved part of the aortic arch, becomes the arterial bundle. It connects the pulmonary trunk (or left pulmonary artery) with the aortic arch.